The future water supply of Birmingham - Barclay, Thomas (Cornish Brothers ; Simpkin, Marshall, 1898)
In this title the first section outlines the reasons for undertaking the scheme which led to the passing of the 1892 Birmingham Corporation Water Act. The following sections cover: the passing of the Act; the Liverpool, Manchester and London water supplies; provisions made for the interim water supply of Birmingham; the works and reservoir construction in the Elan Valley and at Frankley; an update on work on the aqueduct.
Keywords: Water-supply -- England -- Birmingham.; elektronické knihy; electronic books